Ocular Effects of Glycyrrhizin at Acidic and Neutral pH - Somayajulu, Mallika; McClellan, Sharon A.; Bessert, Denise A.; Pitchaikannu, Ahalya; Hazlett, Linda D. (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose: To test effects of acidic vs neutral pH glycyrrhizin (GLY) on the unwounded and wounded normal mouse cornea and after infection with P. aeruginosa isolates KEI 1025 and multi-drug resistant, MDR9. Methods: Acidic or neutral GLY vs PBS was topically applied to normal or wounded corneas of C57BL/6 mice. In unwounded corneas, goblet cells and corneal nerves were stained and quantitated. After wounding, corneas were fluorescein stained, and photographed using a slit lamp. Mice also were infected with KEI 1025 or MDR9 and the protective effects of GLY pH evaluated comparatively. Results: In the unwounded cornea, application of acidic or neutral GLY vs PBS reduced the number of bulbar conjunctival goblet cells, but did not alter corneal nerve density. Similar application of GLY to scarified corneas delayed wound closure. After KEI 1025 infection none of the GLY vs PBS treated corneas perforated; GLY treatment also decreased plate count (neutral pH more effective), reduced MPO and several cytokines. Similarly, for MDR9, GLY at either pH was protective and also enhanced the effects of moxifloxacin to which MDR9 is resistant. Conclusion: Acidic or neutral pH GLY decreased goblet cell number, but had no effect on nerve density. After corneal wounding GLY at either pH: 1) delayed wound closure; and 2) after infection, decreased keratitis when used alone or in combination with moxifloxacin. Neutral pH did not alter the therapeutic effect of GLY and would be preferred if used clinically.